Transplacental transfer of venlafaxine evaluated by ex vivo perfusion. (January 2022) - Hirschmugl, Birgit; Wadsack, Christian
Abstract: Introduction: Depression is frequent among pregnant women and decision for treatment with antidepressants needs careful consideration of risks for the fetus. Since data regarding fetal antidepressant exposure are rare, we aimed to evaluate transplacental transfer of venlafaxine, a selective norepinephrine reuptake inhibitor. Methods: Ex vivo human placental perfusion experiments were conducted in double closed set-up. Venlafaxine (18.1 ± 2.1 μg/L) was offered in maternal circuit and maternal-to-fetal transfer was monitored over a period of 3h. Venlafaxin and O-desmethylvenlafaxine concentrations were determined by HPLC-MS in maternal and fetal perfusion medium. Results: We observed maternal-to-fetal transfer of venlafaxine within 5 min perfusion. The concentration equilibrium was approximated between maternal (7.5 ± 0.5 μg/L) and fetal (6.5 ± 0.6 μg/L) compartment at time point 180 min, which corresponds to a fetal-maternal (FM) ratio of 0.89. Discussion: Our results are comparable with in vivo data from an observational study which emphasizes that the ex vivo placental perfusion model is suitable for systematic evaluation of fetal antidepressant exposure. Highlights: Rapid maternal-to-fetal transfer of venlafaxine in presence of physiological HSA concentrations was observed. Venlafaxine approximates steady state between maternal and fetal compartment after 3h ex vivo placental perfusion. Venlafaxine FM ratio in ex vivo experiments is comparable to observational studies.